Directions of changes in match structure in female wrestling based on World Wrestling Championships 2014 and The Olympic Games 2016 observations - Kruszewski, A.; Kruszewski, M.; Kuzmicki, S.; Tabecki, R. (Archives of Budo Science of Martial Arts and Extreme Sports, 2019)
Background & Study Aim In all sport disciplines, the simplest and the most commonly used method of the athlete level evaluation, or theirs progress in sport competition is observation. The aim of study was knowledge about current trends of changes in structure of matches in female wrestling, through similarities and differences identification of technical activities performed during World Wrestling Championships (Tashkent, Uzbekistan 2014) and the Olympic Games (Rio De Janeiro 2016).